Alternative designs for tariffs on embodied carbon. A global cost-effectiveness analysis - Christoph Böhringer; Brita Bye; Taran Fæhn; Knut Einar Rosendahl (Statistics Norway, Research Department, 2012)
In the absence of effective world-wide cooperation to curb global warming, import tariffs on embodied carbon have been proposed as a potential supplement to unilateral emissions pricing. We consider alternative designs for such tariffs, and analyze their effects on global welfare within a multi-region, multi-sector computable general equilibrium (CGE) model of global trade and energy. Our analysis suggests that the most cost-efficient policy could be region-specific tariffs on all products, based on direct plus electricity emissions. In the end, however, the potential cost savings through carbon tariffs must be weighed against the administrative costs as well as legal issues and political considerations.
Keywords: Q43; Q54; H2; D61; 330; carbon leakage; embodied carbon; border tariffs